Pemanfaatan Aplikasi Approling Sebagai Instrumentasi Dalam Penyusunan Program Bimbingan dan Konseling di Sekolah - Nazila Syifa Thohiroh; Devi Anggraini; Devi Fitriana; Simar Simar; Farah Syaharani; Umi Laelatul Khasanah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This journal reviews the use of various kinds of instruments that make it easier for Guidance and Counseling teachers to develop BK programs in schools. This study aims to analyze data related to the implementation of the Guidance and Counseling program in schools by using several supporting instruments. The instruments used in the preparation of the guidance and counseling program include the AKPD (Student Needs Questionnaire), DCM (Problem Check List), and the Approling Application. For the use of AUM it is rarely used because it has been facilitated by other alternatives in the form of more effective applications. This type of research is qualitative research using a structured (written) interview method, namely by first compiling a number of questions to ask the informant with the aim of gathering as much information as possible. The results of the study show that of the various existing instruments, the approximation application is more widely used because it makes it easier for guidance and counseling teachers to develop programs quickly and accurately. Due to the existence of this application, there is no need to use the manual method and the data obtained is also complete, neatly arranged and the contents are very detailed.